Changing Epidemiology of Pediatric Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs)
Neurosurgeons at the Hospital for Sick Children, Toronto, Canada, analyzed and classified 1, 866 surgical pathology cases of brain tumors in children under age 19 years, treated 1980-2008.